A novel cloud auditor based trust management framework for cloud computing. (2016) - Sidhu, Jagpreet; Singh, Sarbjeet
The adoption of cloud computing transfers control of resources to Cloud Service Providers (CSPs). This gives rise to a variety of security and privacy issues. It has become incredibly complex for CCs to make distinction among similar kinds of services offered by different service providers. The proposed framework evaluates trustworthiness of service providers by evaluating compliance between monitored Quality of Service (QoS) parameters and QoS agreed in Service Level Agreement (SLA). The compliance values are processed using a technique known as analytical hierarchical process to obtain the trust of service providers. To validate the design objective of framework, i.e. the formation of trust by evaluating compliance of services, a case-study-based approach has been followed. The proposed framework can be employed in real cloud environment to establish trust which can help CCs in selecting the most trustworthy service providers in this relatively new distributed computing environment.